Synthesis of carbon-encapsulated iron nanoparticles by pyrolysis of iron citrate and poly(vinyl alcohol): a critical evaluation of yield and selectivity - Bystrzejewski, Michał; Klingeler, Rüdiger; Gemming, T.; Büchner, B.; Rümmeli, M. H. (Nanotechnology, 2011)
Carbon-encapsulated iron nanoparticles were synthesized by pyrolysis at 1000 °C of two solid precursors: poly(vinyl alcohol) and iron citrate. The weight ratio between the precursors controlled the reaction yield, crystallinity, morphological features and magnetic properties of the products. The encapsulation yield of iron nanoparticles in carbon shells was strongly influenced by the iron-to-carbon ratio and depended on the iron citrate content in the initial reactant mixtures. Despite the inherent simplicity of the process and the use of low cost starting materials the demonstrated route possesses limited selectivity, especially at high iron-to-carbon ratios. At these experimental conditions the as-obtained products contained non-encapsulated Fe particles and graphite in addition to magnetic carbon encapsulates. These by-products were effectively removed by a one-pot purification procedure that included acid treatment.